2011
DOI: 10.2112/si59-030.1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Aeolian Saltation: A Comparison of Sensors

Abstract: SHERMAN, D.J.; LI, B.; FERRELL E.We report the results of fteld experiments designed to cotnpare four types of aeolian saltation setisors: the Saftre; the Wenglor® Particle Counter; the Miniphone; and the Buzzer Disc. Sets of sensors were deployed in tight spatial an-ays and sampled at rates as fast as 20 kHz. In two of the three trials, the data from the sensors are compared to data obtained from sand traps. The Miniphone and the Buzzer Disc, based on microphone and piezoelectric technologies, respectively, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 34 publications
0
52
1
Order By: Relevance
“…[], and Sherman et al . []. The Wenglor LCPs have a switching capacity of 10 kHz, but as particle concentration increases during more intense transport periods, the probability of grain overlap increases, which may yield a single count for two or more particles passing through the beam in unison.…”
Section: Experimental Designcontrasting
confidence: 49%
“…[], and Sherman et al . []. The Wenglor LCPs have a switching capacity of 10 kHz, but as particle concentration increases during more intense transport periods, the probability of grain overlap increases, which may yield a single count for two or more particles passing through the beam in unison.…”
Section: Experimental Designcontrasting
confidence: 49%
“…As for Saltiphone acoustic impact sensors, wind tunnel observations by Sterk et al (1998) indicated consistent sensor mass flux responses in comparison to traps, whereas Goossens et al (2000) showed that these sensors provide inconsistent results with changing wind speed, especially for coarser grain-size fractions. Wenglor optical counters appear to provide the most consistent particle counts over a reasonably wide range of saltation intensities (Hugenholtz and , and, in contrast to past suggestion (e.g., Sherman et al, 2011), optical sensor saturation appears not to be a problem (Sec. 4.2).…”
Section: High-frequency Instrument Selectionmentioning
confidence: 84%
“…To better resolve turbulence-induced saltation fluctuations, a variety of new HF sensors have been deployed in field studies over the past two decades (e.g., Baas, 2004; Barchyn and Hugenholtz, 2010;Sherman et al, 2011). HF measurements typically register individual sand grains, using sensors with optical gates (e.g., Hugenholtz and Barchyn, 2011;Etyemezian et al, 2017), piezoelectric impact plates (e.g., Barchyn and Hugenholtz, 2010;Sherman et al, 2011), or acoustic microphones (e.g., Spaan and van den Abeele, 1991;Ellis et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Wenglors were mounted on one or two fixed vertical arrays (Martin et al, ), with a maximum spanwise separation among sensors of 1.3 m. Though numbers and heights of Wenglors, and thus corresponding measurements of total saltation number counts (Bauer & Davidson‐Arnott, ; Hilton et al, ), varied among field sites and deployment days (Martin et al, ), we are concerned here only with the frequency of occurrence of saltation. Based on the observed constant vertical shape of saltation profiles (Martin & Kok, ) and the fact that Wenglor sensor saturation (e.g., Hugenholtz & Barchyn, ; Sherman et al, ) appears to be absent (Martin et al, ), we assume that differences in Wenglor heights among deployments affect only the possibility of false negatives (i.e., potential under‐detection of saltation frequency), and we correct for this by treating particle arrivals as a Poisson process (see Appendix A).…”
Section: Methodsmentioning
confidence: 99%